Nanobodies: Next Generation of Cancer Diagnostics and Therapeutics - Yang, Emily Y.; Shah, Khalid (Frontiers in Oncology, 2020)
The development of targeted medicine has greatly expanded treatment options and spurred new research avenues in cancer therapeutics, with monoclonal antibodies (mAbs) emerging as a prevalent treatment in recent years. With mixed clinical success, mAbs still hold significant shortcomings, as they possess limited tumor penetration, high manufacturing costs, and the potential to develop therapeutic resistance. However, the recent discovery of “nanobodies”, the smallest-known functional antibody fragment, has demonstrated significant translational potential in preclinical and clinical studies. This review highlights their various applications in cancer and analyzes their trajectory towards clinical translation.